Wi-Jun-Jon. An Assinneboin Chief - Going to Washington - Returning to his home (From Catlin's N.A. Indian Collection) / Catlin del on Stone by McGahey. - Catlin, George, 1796-1872 artist. (William L. Clements Library Image Bank, 1844)
Two full-length portraits of Wi-Jun-Jon. The portrait on the left shows Wi-Jun-Jon as he was during a journey to Washington D.C. in 1832, dressed in a shirt and leggings both made of mountain goat skin and decorated with porcupine quills, mocassins, a war bonnet made of eagle feathers and a buffalo skin robe lined with the hair of scalped enemies. The portrait on the right shows Wi-Jun-Jon returning home after his trip to Washington D.C., smoking a cigarette, holding two bottles of what is presumably whiskey in his back pockets and dressed in a blue European-style military suit adorned with golden epaulettes, a broadsword, white gloves, a tall beaver hat crowned with a red feather, a silver waistband, and high-heeled boots while holding a blue umbrella in one hand and a white fan in the other. In the background of the former portrait the city of Washington D.C. is visible, whereas in the background of the latter portrait multiple tipis are present.